PERTUMBUHAN DAN HASIL KORO PEDANG PUTIH (Canavalia ensiformis L.) PADA PEMBERIAN MACAM INOKULAN RHIZOBIUM DAN DOSIS UREA DI LAHAN PASIR - Maria Theresia Darini; Lilik Kusdiarti (Program Studi Agroteknologi INSTIPER, 2017)
The research aims to study of growth and yield jack bean (Canavalia ensiformis L.) as the substitution of soybean plants on the application of different inoculants and doses of urea fertilizer, has been carried out in Depok, Kretek, Bantul Special Region of Yogyakarta. The research was a factorial experiment arranged in Randomized Completly Block Design with four replications. The first factor was kind of inoculants, consists of two kinds: peanut and soybean Rhizobium inoculants, the second factor was doses of urea fertilizer consisted of three levels 25; 50 and 75 kg per ha. Observation variables include the number of root nodules, height of plant, fresh and dry weight of plants aged 6 and 10 weeks, the number and weight of pods, weight of seeds per plot, the index growth, absolute growth rate, harvest index and yield per hectare. Data were analyzed by analysis of variance followed by Duncan’s Multiple Range Test of 5 % significant level. Conclusion there was no interaction between kind of inoculants and doses of urea fertilizer of all variables. Inoculants do not enhance the growth and yield of jack bean, while the urea fertilizer of 75 kg urea per hectare improving growth and yield jack bean increase amounted to 42.64% of the application fertilizer urea 50 kg per ha.